THE POWER OF BODY LANGUAGE IN HUMAN COMMUNICATION - Toshmirzayeva Sitora; To'raqulova Sobira; Sattorova Sabohat (TADQIQOTLAR, 2025)
Abstract This  article  explores  the  significance  of  body  language  in  human communication.  It  investigates  how  non-verbal  cues,  including  facial  expressions, gestures,  eye  contact,  and  posture,  contribute  to  the  communication  process.  By examining both universal and culture-specific body language, this paper explains the advantages  of  understanding  non-verbal  signals  and  their  practical  applications  in everyday and cross-cultural contexts.